Cluster of Learning Models (Information Processing Model and Behavioral Model) - Naufalia, Habshi; Istiqomah, Istiqomah; Muhibbin, Much Ihsaanul; Khuriyah, Khuriyah (The Future of Education Journal, 2024)
This study aims to analyze two learning models, namely the Information Processing Model and the Behavioral Model, as well as their implications in the educational process. Using a literature review method with a qualitative approach, this research examines the theories, principles, and applications of both models based on relevant literature. The Information Processing Model emphasizes students' cognitive processes, such as problem-solving and information processing, while the Behavioral Model focuses on behavior formation through reinforcement and observable behavior modification. The results indicate that both models have unique characteristics that can be adapted according to the goals, content, and conditions of the learners. Proper application of these learning models can enhance the effectiveness of teaching and learning by optimally meeting students' needs.